The Level of Understanding about Contraceptive and Human’s Reproduction System among University Students. - Lukman@Zawawi, Mohamad; Azlini, Chik; Normala, Riza (2018)
The objective of this research is to determine the level of knowledge of the female students of Universiti Sultan Zainal Abidin (UniSZA) about the reproductive system and contraception methods. A questionnaire was used as an instrument to collect basic data among UniSZA female students on their knowledge about the reproductive system and human contraceptive methods. The study sample consists of 350 female students aged 18 to 26 years old. The survey instrument consisted of 24 items divided into two parts. The first part had 10 questions and the second part had 14 questions of the reproductive system and contraceptive methods. A-24 item Miller-Fisk Sexual Knowledge Questionnaire asked for general feedback regarding the questionnaire. The questions pertained to the areas of demographics and sexual knowledge regarding the reproductive system and contraceptive methods. The analysis of this study uses the discriminant analysis (DA) controls the variables that separate among two or more clearly joined group or cluster. The results obtained in the three significant valueand mean (p < 0.05) that the student has the highest level of sexual knowledge pertaining to the reproductive system and contraceptive methods.